URBAN ECOTOURISM TO REDUCE TOURISM IMPACT ON AIR QUALITY OF BANDUNG CITY - Yani Adriani (Centre For Tourism Planning and Development, 2013)
The development of tourism in Bandung over the past decade caused both a positive and a negative impact on social and environmental aspects. Concentration of tourist activity which spread across many parts of the city could be a source of congestion and air pollution now and in the future.Negative impacts of tourism on the environment in Bandung city was also suffered by the people. Awareness of people and tourist concerning the importance of a healthy, comfortable, and sustainable environment in the future could encourage community spirit to develop Bandung urban tourism which are high quality and environmentally sound. The urban ecotourism is a concept in which tourism development is expected to meet the expectations of the community and tourists in the development of Bandung tourism that has taken the quality of the environment, society, and tourists into consideration. The diversity of tourist attraction in Bandung could provide broad opportunities for the development of urban ecotourism in Bandung. Development of six urban ecotourism areas is expected to reduce the negative impact of tourism, particularly on declining air quality.